Clinical Characteristics of Intussusception in Children Admitted to Prof. Dr. R. D. Kandou Hospital - Lampus, Harsali F.; Rawung, Rangga B. V.; Lengkong, Andriessanto C.; Bunu, Edwin (Medical Scope Journal, 2025)
Abstract: Intussusception is a medical condition in which a part of the intestine folds into an adjacent section, causing obstruction, vascular compromise, and potential bowel necrosis if left untreated. This study aimed to analyze the characteristics of intussusception cases at Prof. Dr. R. D. Kandou Hospital, Manado. This was a retrospective and descriptive study using medical records of pediatric intussusception cases treated in the division of pediatric surgery, Prof. Dr. R. D. Kandou Hospital, Manado, from January 2019–December 2024. The information collected included age, gender, onset from obstruction syndrome until the patient was brought to the emergency department, type of surgery, ventilator use, length of stay in PICU, length of nutritional parenteral, and length of hospitalization. All calculations were executed using Microsoft Office Excel 2021 and SPSS 25.0. The results obtained 32 cases; the dominant gender was female (51.5%). Most of the patients were ≤2 years (63.6%), with the highest age being 204 months or 17 years old and the lowest age being 2 months. The most frequent cases had onset of obstructive syndrome of ≤24 hours (51.5%). All patients underwent exploratory laparotomy; 16 patients (50%) required milking, while 16 patients (50%) required resection anastomosis. Follow up after surgery revealed that most patients used ventilator (72.7%), stayed in PICU ≤7 days (69.7%), got ≤7 days of parenteral nutrition (78.8%), and were hospitalized for >7 days (69.7%). In conclusion, intussusception mainly affects children <2 years old, predominantly female, abdominal pain as the prominent chief complaint, and hospitalized for more than seven days after undergoing surgery. Keywords: intussusception; management; laparotomy; outcome